Distribution of new cars: No longer an issue for EU competition law? - Václav Šmejkal (Review of Economic Perspectives, 2021)
Distribution cartels in the automotive sector used to be frequently dismantled and sanctioned by the European Commission and the EU Courts still some 15 years ago. In recent years, however, only a few cases have been reported at the national level of EU Member States. Is it because the distribution of new cars really ceased to be a competition problem as the European Commission declared when it removed this part of the automotive business from the specific Block Exemption Regulation for the automotive sector in 2010? The purpose of the present analysis is first to inspect the car distribution cases that emerged in the EU after the year 2000 and, second, to speculate somewhat whether new forms of distribution, brought by the digitalization of marketing and sales, cannot bring about also new risks to cartel agreements and other types of distortions of competition in car sales.
Keywords: L42; K21; K42; 330; EU competition law; distribution of new cars; vertical cartels; na tional competition authorities